Influenza Vaccination as a Novel Trigger of Wells Syndrome in a Child. Issue 4 (20th April 2015) - Simpson, Jacqueline K.; Patalay, Rakesh; Francis, Nicholas; Roberts, Nerys
Abstract Wells syndrome is a rare disorder of unknown etiology. Precipitants include insect bites, infections, medications, malignancies, and vaccinations. Possible mechanisms include hypersensitivity reactions to antigens. There are four reports in the literature of Wells syndrome precipitated by vaccinations (hepatitis B vaccine, tetanus vaccine, tetanus‐diptheria vaccine and triple antigen vaccine). We present a further case of Wells syndrome in a 22‐month‐old child after influenza vaccine as a novel trigger not previously reported.